All that glisters is not gold: sampling-process uncertainty in disease-vector surveys with false-negative and false-positive detections. - Fernando Abad-Franch; Carolina Valença-Barbosa; Otília Sarquis; Marli M Lima (Public Library of Science (PLoS), 2014)
Vector-borne diseases are major public health concerns worldwide. For many of them, vector control is still key to primary prevention, with control actions planned and evaluated using vector occurrence records. Yet vectors can be difficult to detect, and vector occurrence indices will be biased whenever spurious detection/non-detection records arise during surveys. Here, we investigate the process of Chagas disease vector detection, assessing the performance of the surveillance method used in most control programs--active triatomine-bug searches by trained health agents.Control agents conducted triplicate vector searches in 414 man-made ecotopes of two rural localities. Ecotope-specific 'detection histories' (vectors or their traces detected or not in each individual search) were analyzed using ordinary methods that disregard detection failures and multiple detection-state site-occupancy models that accommodate false-negative and false-positive detections. Mean (± SE) vector-search sensitivity was ∼ 0.283 ± 0.057. Vector-detection odds increased as bug colonies grew denser, and were lower in houses than in most peridomestic structures, particularly woodpiles. False-positive detections (non-vector fecal streaks misidentified as signs of vector presence) occurred with probability ∼ 0.011 ± 0.008. The model-averaged estimate of infestation (44.5 ± 6.4%) was ∼ 2.4-3.9 times higher than naïve indices computed assuming perfect detection after single vector searches (11.4-18.8%); about 106-137 infestation foci went undetected during such standard searches.We illustrate a relatively straightforward approach to addressing vector detection uncertainty under realistic field survey conditions. Standard vector searches had low sensitivity except in certain singular circumstances. Our findings suggest that many infestation foci may go undetected during routine surveys, especially when vector density is low. Undetected foci can cause control failures and induce bias in entomological indices; this may confound disease risk assessment and mislead program managers into flawed decision making. By helping correct bias in naïve indices, the approach we illustrate has potential to critically strengthen vector-borne disease control-surveillance systems.